MEMBRAN KOMPOSIT POLYVINYLIDENE FLUORIDE/ TITANIUM DIOKSIDA UNTUK PENGOLAHAN LIMBAH CAIR INDUSTRI KELAPA SAWIT - Agustina; Erna Yuliwati; Mardwita (LPPM Politeknik Jambi, 2019)
The aim of this research is to develop membrane material and analyse the membrane performance in liquid waste management of CPO industry to separate suspended solids. Conventional waste treatment has not been able to reach the minimum regulatory standards that have been set. Land area constraints and waste management techniques are complex and produce large sludge volumes. Besides specifically for managing liquid organic waste, the difficulty of the process of degradation of waste due to the high quantity and content of contaminants that can reach up to 40,000-120,000 mg / l for COD. In this study composite membrane made by titanium dioxide in the membrane polyvinylidene fluoride was blend very well and suited to remove suspended solids in the wastewater. The optimization result obtained is the addition of TiO2 2% produce maximum flux with the value of 180 L / m2.hr and the percentage of 92% fitration. The results of the filtration process conditions were the total suspended solids (TSS) by 99.63% and ammonium nitrogen (NH3-N) by 92.82% is the ABFR process conditions at 2.25 ml / min, HRT at 276.93 min, MLSS concentration at 4.50 g / L, and the pH at 6.50. So it can be concluded that titanium dioxide resulted the minimise of average poresize and enhance the hydrophilicity of membrane that resulted the maximum flux of this process.